Measurement of branching fractions and rate asymmetries in the rare decays β→[kappa](*)l+l- - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
In a sample of 471×106 B¯¯¯B events collected with the BABAR detector at the PEP-II e+e− collider we study the rare decays B→K(*)ℓ+ℓ−, where ℓ+ℓ− is either e+e− or μ+μ−. We report results on partial branching fractions and isospin asymmetries in seven bins of dilepton mass-squared. We further present CP and lepton-flavor asymmetries for dilepton masses below and above the J/ψ resonance. We find no evidence for CP or lepton-flavor violation. The partial branching fractions and isospin asymmetries are consistent with the Standard Model predictions and with results from other experiments.